Cost-Volume-Profit (CVP) Analysis of Nepalese Commercial Banks - Kunwar, Birendra; Poudel, Shiva Raj (Contemporary Research: An Interdisciplinary Academic Journal, 2025)
The paper uses the Cost-Volume-Profit (CVP) model to compare the profitability structure and operational practices of two big banks of Nepal Everest Bank Limited (EBL) and Sanima Bank Limited (SANIMA). Using the audited financial data from the period from FY 2014/15 to 2023/24, the study has a quantitative, longitudinal design. Within the CVP framework, Total Operating Income is the sales, Interest Expenses equals the variable costs and Operating Expenses equals the fixed costs. On the basis of this, the study calculates and compares important parameters: Contribution Margin Ratio (CMR), Break-Even Point (BEP), Margin of Safety (MOS) and Degree of Operating Leverage (DOL). The analysis demonstrates that both the banks have developed steadily towards sustainable growth with stable cost structures. EBL's CMR is on average ten percentage points higher than SANIMA's, and the difference is significantly higher, reflecting a stronger structure in terms of profitability. However, variations in BEP, MOS and DOL are not statistically significant and would indicate similar operational resilience and risk exposure. EBL's superior profitability is attributed to structural efficiency; on the other hand, SANIMA gains competitiveness through disciplined cost management. Implications: The implications of the study are that it is possible to achieve stability of operations in commercial banking through the application of different strategic approaches - either through a high margin structure or by exercising strong cost control. The CVP framework provides a useful diagnostic tool for bank managers to determine core profitability (via CMR) and financial resilience (via MOS), and goes beyond traditional analysis of performance by going beyond conventional banking ratios.